GEOGRAPHY OF DARK TOURISM IN THE WORLD - LUSHCHYK, Mariya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article emphasizes that the issue of «dark» tourism is insufficiently studied in scientific sources, but it is already attracting interest in science and society. A short author’s analysis of the materials of modern scientific research and research on theoretical and practical aspects of the development of «dark» tourism in the world by foreign and domestic scientists was carried out. The resource base for the development of «dark» tourism in the world was studied. A list of 57 potentially popular tourist «dark» places and objects («dead cities» and places of alienation, medieval castles, dungeons, catacombs, thematic museums, prisons, barracks, hospitals, cathedrals, ancient settlements, cemeteries, sanctuaries , anomalous zones, places of power, objects or territories of natural phenomena and disasters, battlefields and battles, etc.), which can be used in the development of new tourism products. According to monitoring data, a map scheme of «dark» tourism objects has been completed. Geographical (by macro-regions of the world) and thematic (by objects belonging to specific types of dark tourism: mystical tourism, necropolis tourism, thanatotourism and disaster tourism) structuring of these objects was carried out, and regularities in their geospatial organization were revealed. The most interesting objects of dark tourism in the regions of the world are highlighted and a brief description of several destinations is given. It is noted that the study of objects of «dark» tourism can be useful in the process of forming strategies for the development of tourism in countries and regions, in the arrangement of infrastructure of the appropriate profile (quest rooms, amusement parks, thematic entertainment centers), in the organization of cultural events, contests, quests, festivals , educational excursions in mystical places to popularize them among tourists and attract additional investments, in the activities of tourist enterprises that plan to expand the existing range of tourist programs. The importance of further research on dark tourism is emphasized, as it is designed to stimulate humanity to realize the scale of disasters, to recognize the need for a peaceful relationship between people, science, military and nuclear technologies, which sometimes endanger the existence of the entire human civilization, and which makes clear the errors of these events and tragedies of the past and present.